The Impact of Unlicensed Research Software Consumer Usage Behaviour on Perceived University Reputation Among Postgraduate Students in Malaysia - Arman, Ahmad (2024)
Unlicensed research software usage among students is a global crisis against higher learning institutions. The phenomenon has affected the perception, expectation, and trust of stakeholders and societies toward the university’s branding and reputation simultaneously and could tarnish the long-term sustainability and credibility of the higher learning institutions. The purpose of this study is to explore, expose and deploy the significant antecedents (factors) that cause the usage of unlicensed research software among post-graduate students in Malaysia and simultaneously measure the perceived reputational impacts of their deviant behaviour towards their institutions using the Unified Theory of Acceptance and Use of Technology (UTAUT) with an extension of perceived university reputation as the dependent variable (post-antecedent of behaviour). Multi-sampling through a combination of Purposive and Snowball sampling was used to gather all 420 respondents’ primary data through an online questionnaire. The PLS-SEM were used for the analysis of the information collected. To wind up, the students’ economic conditions, performance expectancy, and facilitating condition, have a positive relationship with the intention to use unlicensed research software among the postgraduate (PhD and Doctoral) students in Malaysian universities. All exogenous are also fully mediated by the intention to use the unlicensed research software and the usage behaviour could mediate the relationship between the intention to use and facilitating condition towards the perceived reputation of the university. The usage behaviour also has a positive relationship with the perceived university reputation suggesting that individual choices around unlicensed research software use could have broader implications for institutional credibility. Finally, the tested model shows a range of predictive performances across different constructs, with some exhibiting high predictive relevance, suggesting the model's strength in forecasting these particular outcomes. Understanding this unlicensed research software usage intention and behaviour as well as its impacts on the university’s reputation issue helps Malaysia to develop an ethical, better and higher quality education system to nurture better citizens for the future. The national aspiration to make Malaysia the excellent education hub in Southeast Asia and a highly reputable education region will be accomplished when the issue of unlicensed research software usage is curbed and controlled through a comprehensive understanding of its antecedents and consequences. It could also help local universities inculcate a more ethical education environment and culture to produce more ethical postgraduate students who will lead the future of the country, society, and the national economy to be more prosperous.